(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Clause is devoted to questions to application virtual technologies in educational process and revealing of opportunities of use of virtual means in educational process. Besides in clause the efficiency is listed and the role of virtual means used in educational process is underlined.